Flexibilidad laboral y su incidencia en la rentabilidad del Proyecto Hidroenergético Central Hidroeléctrica Marañón, de la empresa Hydro Power Andina EIRL - Robles Solórzano, Melissa Geraldine (2017)
The purpose of this research is to propose a very common theme in service companies, which is to measure labor costs without affecting the level of profitability in the Hydro Power Plant Central Hydroelectric Project Marañón of Hydro Power Andina EIRL, the district of Trujillo. When analyzing the labor aspect of the company, different working days were found, according to the personal and professional situation of the worker; evidence can be found of the high labor costs of a private activity regime; and consequently assume the impact on profitability (profit), being affected by the various labor obligations. The research is based on information collected from the company, from which data such as labor costs for personnel transportation, food expenses, accommodation expenses, training, contributions to ESSALUD, ONP, AFPs, social benefits, overtime, gratuities, CTS; which if they influence the profitability of the projects. Likewise, it has been possible to know the existing incidence of the current labor legislation of the company, the same in which in recent years has been implemented with more parameters for their due compliance, always seeking the well-being of their employees. All this combined and interacting synergistically must provide the company with a high degree of profitability at the project level, a capacity that will allow to face and adapt to future work and to the changes of the world today in the process of globalization. In addition to this, this research seeks to demonstrate the relationship between labor flexibility in organization and profitability in the C.H. Marañón, which resulted in an improvement in the profit margin, more efficient processes and increased capacity to respond to the growth of the company Hydro Power Andina EIRL, in the district of Trujillo.